Sebaceous Tumors of the Skin: A Study of 145 Lesions From 136 Patients Correlating Pathologic Features and DNA Mismatch Repair Staining Pattern - Konstantinova, Anastasia M; Kastnerova, Liubov; Michal, Michal; Kolm, Isabel; Kazakov, Dmitry V (The American Journal of dermatopathology, 2021)
Sebaceous neoplasms occur sporadically or in the setting of Muir-Torre syndrome. The data regarding the correlation of pathologic features and DNA mismatch repair (MMR) staining pattern in sebaceous tumors of the skin are very scanty and based on relatively small series of patients. The goal of this study was to correlate MMR staining pattern with selected morphological features in a series of 145 sebaceous neoplasms (sebaceous adenoma, sebaceoma, and extraocular sebaceous carcinoma) from 136 patients. Cystic change, intratumoral mucin deposits, squamous metaplasia in the absence of keratoacanthoma-like changes, ulceration, intratumoral and peritumoral lymphocytes (in cases without epidermal ulceration), and intertumoral heterogeneity proved to be significantly associated with MMR deficiency. Identification of any of these changes, alone or in combination, should prompt further investigation of the patient to exclude Muir-Torre Syndrome. Our study also confirms the previously published observation that the diagnosis and tumor location are significantly associated with MMR deficiency.
Keywords: senioři; nádory hlavy a krku; skalp; DNA-Binding Proteins; obličej; senioři nad 80 let; mismatch repair endonukleáza PMS2; nádory mazových žláz; mladiství; imunohistochemie; Middle Aged; mužské pohlaví; Head and Neck Neoplasms; adenom; MutL Protein Homolog 1; oprava chybného párování bází DNA; mladý dospělý; Adult; MutL homolog 1; Adenoma; Carcinoma; Aged, 80 and over; Immunohistochemistry; homolog 2 proteinu MutS; Young Adult; ženské pohlaví; DNA Mismatch Repair; Mismatch Repair Endonuclease PMS2; Humans; Face; Sebaceous Gland Neoplasms; Extremities; lidé středního věku; DNA vazebné proteiny; dospělí; MutS Homolog 2 Protein; Scalp; Female; Aged; končetiny; trup; Adolescent; Torso; lidé; Male; karcinom